2020
DOI: 10.1111/ctr.14010
|View full text |Cite
|
Sign up to set email alerts
|

Strict selection criteria in uncontrolled donation after circulatory death provide excellent long‐term kidney graft survival

Abstract: Background: We aimed to report our experience in uncontrolled donation after circulatory death (uDCD) kidney transplantation applying a strict donor selection and preservation criteria. Methods: All kidney recipients received a graft from a local uDCD. As controls, we included all renal transplants from local standard criteria donation after brain death (SDBD) donors. Normothermic regional perfusion was the preservation method in all cases. Results: A total of 19 kidneys from uDCD donors were included and 67 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 29 publications
0
31
0
1
Order By: Relevance
“…32,34 Fibrin thrombi have also been reported in kidneys from donors with disseminated intravascular coagulation and naturally in 3%–9% of organs from DBD. 19,35–37 Transplantation often results in DGF in these kidneys, 2,6–14,35,36 although a study from the Mayo Clinic, despite a significant difference in vascular resistance and arterial flow at evaluation, no significant difference in DGF was observed, although the control material had 39% and the study group had 49% DGF, that is, higher levels than more commonly reported. 37 Based on these and other studies in experimental animals and humans 21,38–40 as well as our early investigational studies, we selected a combination of Lys-plasminogen and tPA for perfusion and reconditioning of uDCD kidneys.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…32,34 Fibrin thrombi have also been reported in kidneys from donors with disseminated intravascular coagulation and naturally in 3%–9% of organs from DBD. 19,35–37 Transplantation often results in DGF in these kidneys, 2,6–14,35,36 although a study from the Mayo Clinic, despite a significant difference in vascular resistance and arterial flow at evaluation, no significant difference in DGF was observed, although the control material had 39% and the study group had 49% DGF, that is, higher levels than more commonly reported. 37 Based on these and other studies in experimental animals and humans 21,38–40 as well as our early investigational studies, we selected a combination of Lys-plasminogen and tPA for perfusion and reconditioning of uDCD kidneys.…”
Section: Discussionmentioning
confidence: 87%
“…Organs from circulatory death patients include controlled donations after circulatory death (cDCD) and uncontrolled donations after circulatory death (uDCD). [5][6][7][8][9][10][11][12][13][14] The proportion of donations after circulatory death (DCD) has increased substantially, amounting to 20% of organs from deceased patients in Europe, 2 however, two obstacles remain largely unresolved for uDCD, meaning that this approach tends to be an exception rather than a rule.…”
Section: Introductionmentioning
confidence: 99%
“…19 The in situ preservation of organs with oxygenated blood following the declaration of death and prior to organ recovery was associated with excellent results following uDCDD kidney transplantation. [20][21][22][23][24] Moreover, this approach led to acceptable results with liver transplants despite prolonged periods of warm ischemia inherent to the uDCDD process. [25][26][27] This experience was the driver for an increasing interest on the potential benefits of NRP on liver transplants in the cDCDD setting, where biliary complications, ischemic-type biliary lesions, and graft loss are frequent compared with what observed with livers obtained from donors declared dead by neurologic criteria (DNDD).…”
Section: Discussionmentioning
confidence: 99%
“…NRP was first conceived in Spain to enable the development of the uDCDD pathway 19 . The in situ preservation of organs with oxygenated blood following the declaration of death and prior to organ recovery was associated with excellent results following uDCDD kidney transplantation 20‐24 . Moreover, this approach led to acceptable results with liver transplants despite prolonged periods of warm ischemia inherent to the uDCDD process 25‐27 .…”
Section: Discussionmentioning
confidence: 99%
“…During the last 5 years, the development of cDCDD in Spain is to be highlighted, pioneering the use of NRP with extracorporeal membrane oxygenation (ECMO) devices as an in situ blood reperfusion strategy in both cDCDD 10‐13 and uncontrolled DCDD 14‐16 …”
Section: Introductionmentioning
confidence: 99%